2015
DOI: 10.1016/j.jff.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effects of cocoa fibre on rats

Abstract: The impact of cocoa on microbiota composition, its crosstalk with the immune system and the SCFA production, focusing on the involvement of cocoa fibre were investigated Wistar rats were fed for 3-weeks a standard diet, a diet containing 10%-cocoa (C10), cocoa fibre (CF) or inulin (I).Faecal and serum samples were collected before and after the intervention and caecal content and colon sample were collected at the end. Microbiota composition and IgA-coated bacteria and the SCFA content was quantified. The colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 57 publications
8
52
1
Order By: Relevance
“…As it was previously shown, the faecal concentrations of acetate and propionate were much higher than that of butyrate in rats (Rodríguez-Cabezas et al, 2003). Massot-Cladera et al (2015) observed that the diet containing inulin tended to reduce acetic acid and increase propionic acid proportion with the respect to their initial values as observed in the present study. No effect of JA tuber powder addition into diet on butyric acid concentration in the hindgut was observed in a study by Vhile et al (2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As it was previously shown, the faecal concentrations of acetate and propionate were much higher than that of butyrate in rats (Rodríguez-Cabezas et al, 2003). Massot-Cladera et al (2015) observed that the diet containing inulin tended to reduce acetic acid and increase propionic acid proportion with the respect to their initial values as observed in the present study. No effect of JA tuber powder addition into diet on butyric acid concentration in the hindgut was observed in a study by Vhile et al (2012).…”
Section: Discussionsupporting
confidence: 89%
“…and Bifidobacterium spp. Abhari et al (2015) and Massot-Cladera et al (2015) also observed increased faecal count of these bacteria in inulin-fed rats. The increase in Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 77%
“…Accordingly, several studies have shown that cocoa (58, 75, 76), cocoa flavonoids (58, 77), or cocoa fiber (78) induce changes in gut microbiota composition. Moreover, a lower proportion of IgA-coated bacteria have been observed after cocoa intake (79).…”
Section: Cocoa Intake Influences Intestinal Immune Systemmentioning
confidence: 99%
“…Cocoa‐enriched diets have demonstrated their influence on the gut microbiota and the intestinal immune system, which could be partially attributed to the cocoa's polyphenol and fiber content . As far as we are concerned, no data about the effect of theobromine on gut microbiota and immunity have been published before.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a cocoa‐enriched diet is able to attenuate secretory IgA (S‐IgA) in several intestinal compartments and also the IgA‐coated bacteria proportion in the gut . Moreover, a diet containing 10% cocoa for 6 weeks modifies the intestinal microbiota composition in rats by decreasing the proportion of Bacteroides spp., Staphylococcus spp., and the Clostridium histolyticum subgroup , thus causing a different short‐chain fatty acid (SCFA) production . Similarly, a cocoa diet modulates the intestinal microbiota in orally sensitized rats, as determined by a metagenomics analysis .…”
Section: Introductionmentioning
confidence: 99%